Penguatan Pendidikan Karakter melalui Kegiatan Ekstrakurikuler “Hisbul Wathan” - Budi Santoso (Postgraduate Program Magister Pendidikan Agama Islam, 2018)
The existence of moral degradation causes educational institutions to perform various ways as an effort to provide strengthening Character Education through Extracurricular Activities. One of the activities undertaken in the formal education environment in providing character education development is through Hisbul Wathan activities that must be followed by all students of SMK Muhammadiyah Aimas. This discussion aims to examine and explore information about the development of character education through Hisbul Wathan activities at SMK Muhammadiyah 1 Aimas. The approach used in this research is qualitative with case study method to express and understand the fact that happened intensively and depth related to happened phenomenon. Data and information gathering techniques were conducted through interviews, post-participatory and non-participant observations, documentation studies and literature studies. The results of this research are the forms of activities in Hisbul Wathan activities at SMK Muhammadiyah I Aimas with character education.